Penggunaan Komunikasi Simbolik Tentang Pilpres 2024 Pada Media Sosial X - Aslam, Muhammad; Andung, Petrus Ana; Pietriani, I Gusti Ayu Rina (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2024)
The 2024 Presidential Election in Indonesia presents a number of candidate pairs who are trying to capture public attention through various strategies, including intensive political communication on social media. One of the candidate pairs that has attracted public attention is Anies Baswedan and Muhaimin Iskandar, or often abbreviated as